A Real-Business-Cycle Setup with Habits in Leisure: Lessons for Bulgaria (1999-2022) - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance; Vol 10 No 2 (2024): JMEF, Volume X, Issue 2(19), Winter 2024, 2024)
Habits in leisure a la Kydland and Prescott (1982) are introduced into a real-business-cycle setup augmented with a detailed government sector. The model is calibrated to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2022). The quantitative importance of the presence of habits in leisure is investigated for cyclical fluctuations in Bulgaria, and the ability of this extension to address the wage-hours puzzle in particular. The quantitative effect of habits in leisure is found to be small, and often working in the wrong direction. Hours and wages vary much less than in data, wages are more pro-cyclical, and hours are counter-cyclical. Habits in leisure mechanism is thus not a good candidate to solve the hours-wages puzzle in business cycle literature.